2017
DOI: 10.1002/brb3.703
|View full text |Cite
|
Sign up to set email alerts
|

Evoked potential changes in patients with Parkinson's disease

Abstract: ObjectivePatients with Parkinson's disease (PD) may have sensory dysfunction, and it can be more easily demonstrated through electrophysiologic testing. We aimed to explore whether the impairment of brainstem visual and auditory passageway exists in PD patients using visual evoked potential (VEP) and brainstem auditory evoked potential (BAEP) examinations.MethodsForty‐two PD cases and thirty controls participated in the study. All subjects underwent the VEP and BAEP examinations. The N75, P100, N145 latencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
23
0
2
Order By: Relevance
“…On the other side, the results of Liu et al [13] study showed that the latencies of P100, N75, and N145 were more delayed in patients with PD than controls, but the amplitude of P100 was not significantly different between the PD patients and control subjects. Despite that, the P100 latency was positively correlated with the disease stage.…”
Section: Discussionmentioning
confidence: 83%
“…On the other side, the results of Liu et al [13] study showed that the latencies of P100, N75, and N145 were more delayed in patients with PD than controls, but the amplitude of P100 was not significantly different between the PD patients and control subjects. Despite that, the P100 latency was positively correlated with the disease stage.…”
Section: Discussionmentioning
confidence: 83%
“…The body mass index (BMI) and educational level were recorded. The unified Parkinson's disease rating scale III (UPDRS‐III) was assessed to identify the severity of PD, and the Hoehn and Yahr (H‐Y) classification was used to determine the stage of PD (Liu et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Intergroup comparisons of primary data were performed using the Student's t test and nonparametric tests. The Chi‐square test was used to determine group distribution (Liu et al., ). Pearson's correlation test was used to detect the correlation between CPC variables and the PSQI scores in the PD group.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a reduction of the amplitude of b-waves in PD patients is present at early stages of the disease (Ikeda et al, 1994;Nowacka et al, 2015) (Figure 2B). An increase in the latency of the VEP onset is another frequent finding in PD patients (Tartaglione et al, 1987;Liu et al, 2017;He et al, 2018).…”
Section: Pathological Alterations In the Retina Of Pd Patientsmentioning
confidence: 98%